POTENTIOMETRIC DETERMINATION OF CADMIUM-ACETATE COMPLEXATION IN AQUEOUS SOLUTIONS TO 250°C - Benezeth P.; Palmer D.A. (My University, 2000)
The molal formation quotients of cadmium-acetate complexes were measured potentiometrically (hydrogen-electrode concentration cell) from 50 to 250°C at ionic strengths of 0.1, 0.3, and 1.0 molal in aqueous sodium trifluoromethanesulfonate (NaTr) media. Two cadmium-acetate species, namely Cd(Ac)+and Cd(Ac)2°, were identified by regressional analysis of the data. Their formation quotients were modeled by empirical equations to describe their temperature and ionic strength dependencies. The thermodynamic quantities, obtained by differentiating these equations with respect to temperature at 25°C and at infinite dilution are for Cd(Ac)+: logK1=1.96+/-0.24, ΔH°=-17+/-17 kJ.mol-1, ΔS°=-21+/-53 J.K-1.mol-1 and ΔCp°=660+/-370 J.K-1.mol-1; and for Cd(Ac)2°: logK2=3.15+/-0.10, ΔH°=4+/-14 kJ.mol-1, ΔS°=75+/-47 J.K-1.mol-1 and ΔCp°=-400+/-260 J.K-1.mol-1.
Keywords: POTENTIOMETRY; CADMIUM; ACETATE; FORMATION QUOTIENTS; THERMODYNAMIC PROPERTIES